ANALISIS PENGARUH BIAYA MARKETING TERHADAP SALES VOLUME - Aspizain Caniago; Damdam Damiyana (JURNAL LENTERA BISNIS, 2019)
This study was conducted to determine whether the national marketing costs of vocational colleges have an impact on increasing Sales Volume. The process of acquiring Sales volume is carried out in stages starting from the acquisition of Applicants, Lists and finally Sales Volume which is the number of students ready for college. Data analysis was performed on marketing  data  and  financial  data  over  a  period  of  5  (five)  years,  using  simple linear regression. Based on the calculation results of marketing costs correlation with the acquisition of Sales Volume  is  known  to  be  84.9%,  where  the  value shows  a  meaningful  and very strong relationship, while the results of the coefficient of determination are known that Marketing Costs have a 72.0% influence on the acquisition of Sales Volume, and the remaining 28.0 % is influenced by other factors not examined. The results of calculations using SPSS data analysis obtained linear regression Y= 21762.14+0.00000204X, where Marketing Costs (X) contributed positively to the acquisition of Sales Volume (Y) of 0.00000204 units, and the results  of  the  hypothesis  t  -calculate  is  2.778  values  greater  than  t-table  values  at the significance level of 0.05 (2.778>1.982). Thus the research hypothesis can be accepted that marketing costs have a positive effect on the acquisition of Sales Volume.Keywords: Marketing Costs, Sales Volume